An Analysis of Students’ Reading Comprehension on Report Text Through QAR Strategy - Baihaqi, Muhammad Zidane (English Edu: Journal of English Teaching and Learning, 2024)
This research is a classroom action research that conducted on IX grade students of BaniHasyim Singosari Islamic Junior High School as research subjects. The object of thisresearch is the students' understanding of English, students’ reading literation, and theQAR learning strategy. This research was carried out in one cycle, and each cycleconsisted of 4 stages, namely, planning, action, observation, and reflection. In this study,researchers used observation and tests as data collection methods and qualitativedescriptive analysis as data analysis methods. Data on student learning outcomes wasobtained by conducting pre-test and post-test. The criteria for success set out in this studyare the minimum grade point average equivalent to KKM = 75 and the minimum studentmotivation is high. The results showed 1. The students' reading comprehension andEnglish reading literacy increased with the criteria of at least good, 2. The ability andskills of teachers in English increased with the criteria of at least good, 3. 90% of theeighth grade students of SMP Islam Bani Hasyim already have individual mastery in theability to understand reading (reading comprehension) in English